Development of Bangladesh with equity and justice : immediate tasks for the new government. - Conference on Development with Equity and Justice: Immediate Tasks for the Newly Elected Government (2009 : Dhaka, Bangladesh); Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue, 2009)
Papers presented at the Conference on Development with Equity and Justice: Immediate Tasks for the Newly Elected Government, held at Dhaka, Bangladesh in 2009; organised by Centre for Policy Dialogue, Bangladesh.
Includes bibliographical references.
Keywords: Political rights -- Bangladesh -- Congresses; Infrastructure (Economics) -- Bangladesh -- Congresses; Bangladesh -- Economic policy -- Congresses; Industrial priorities -- Bangladesh -- Congresses